(untitled) (Journal of Partial Differential Equations, 1997)
In this paper a partial answer to the fourth open problem of Bethuel-Brezis- Hélein [1] is given. When the boundary datum has topological degree ± 1, the asymptotic behavior of minimizers of the Ginzburg-Landau functional with variable coefficient 1x_1 is given. The singular point is located.